Pendampingan P5 Tari Nusantara untuk Meningkatkan Keterampilan Kerja Sama Siswa Kelas VII di SMP 8 Palangkaraya - Yuna Yulianti; Zainap Hartati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education has an important role not only in the transfer of knowledge but also in the formation of students' character and social skills, such as cooperation skills. At SMP 8 Palangkaraya, efforts to improve the cooperation skills of grade VII students were made through an arts-based project, namely P5 Tari Nusantara. The project aims to provide direct guidance to students in the learning process, not only in the technical mastery of dance, but also in the development of social skills such as planning, communication, and collaboration. Through this activity, students are expected to be able to develop mutual respect, share responsibilities, and complete tasks effectively in groups. Structured mentoring also involves teachers and parents to ensure the skills taught can be applied in daily life. As a result, the project is expected to be an effective model for improving cooperation skills and enriching students' learning experience at SMP 8 Palangkaraya.